(untitled) (Texas Journal of Engineering and Technology, 2024)
At present, in the process of open mining of ores, mining enterprises need to have information about the hydrogeological conditions of the mine, the flow and level of underground water. Based on research on determining the amount of underground water that has decreased in 2 consecutive stages during the implementation of extraction processes in mining enterprises, the cases of the decrease in the level of underground water in the mine have been proven by means of formulas. In open pit mining, measuring the level of groundwater and determining its direction plays an important role in the extraction of minerals. Water level monitoring in mining operations is related to water flow and level stimulation when a well needs to be installed. If a small diameter production well is satisfactory for use in aquifer testing, it can be installed by connecting lengths of tubing together. jet point and move it forward to the ground through the jet process. When the required depth is reached, the resulting well is completed by raising and pumping. Reactive equipment can be used to obtain underground geological data. It has also proven useful in cleaning and dewatering large diameter wells.